Use of bovine pregnancy-associated glycoproteins to predict late embryonic mortality in postpartum Nelore beef cows - Pohler, K. G.; Peres, R. F.G. [UNESP]; Green, J. A.; Graff, H.; Martins, T. [UNESP]; Vasconcelos, J. L.M. [UNESP]; Smith, M. F. (Elsevier, 2016)
The primary objective was to determine if circulating concentration of bovine pregnancy-associated glycoproteins (bPAGs) on Day 30 after artificial insemination (AI) may serve as a marker of late embryonic mortality in Bos indicus (Nelore) beef cows. In experiment 1, postpartum Nelore beef cows (n = 56) were artificially inseminated at a fixed time (Day 0) after synchronization of ovulation. Serum samples were collected on Days 0, 21, 24, 27, and 30 after AI. The first significant increase (P < 0.0001) in serum bPAGs after insemination occurred on Day 24 of gestation. In experiment 2, ovulation was synchronized in postpartum Nelore beef cows (n = 1460) and AI was received at a fixed time. Pregnancy diagnosis and blood sample collection were carried out on Days 28 to 30 after insemination. Cows that maintained a pregnancy from Days 28 to 100 of gestation (n = 714) had significantly (P < 0.0001) higher circulating concentrations of bPAGs on Day 28 compared with cows that did not maintain a pregnancy (embryonic mortality [EM]) until Day 100 (n = 89). When Day 28 bPAG concentration was included in a logistic regression model to predict pregnancy maintenance until Day 100 of gestation, there was an increase (P < 0.0001) in the probability of maintaining pregnancy as maternal concentrations of bPAGs increased. A receiver operating characteristic curve was generated to determine bPAG concentrations on Day 28 that should predict embryonic survival or mortality with an accuracy of 95% or more. On the basis of the positive and negative predicative value analysis, at Day 28 of gestation a circulating concentration of bPAGs greater than 7.9 ng/mL was 95% accurate in predicting embryonic maintenance (to Day 100); a concentration of bPAGs less than 0.72 ng/mL was 95% accurate in predicting EM by Day 100. In experiment 3, the preceding model was tested in a separate set of Nelore beef cows to validate whether bPAGs would serve as an accurate measure of late embryonic mortality. Ovulation was synchronized in 650 Nelore cows and received AI at a fixed time. Pregnancy diagnosis and bPAG sampling were performed at Day 28 of gestation. Only pregnant cows were included in the analysis. On the basis of the previously reported bPAG cutoff values, the test was 95% accurate in predicting late embryonic mortality at Day 28 of gestation. In summary, bPAGs seem to be a good marker for predicting EM between Days 28 and 100 of gestation and suggest that this model could help dissect the molecular mechanisms leading to late EM.
Keywords: Bovine; Embryonic mortality; Pregnancy; Pregnancy-associated glycoproteins